"n Preek van HCM Fourie na aanleiding van die Oktober-rewolusie in 1917 - Smith, P. D. (Hervormde teologiese studies, 1988)
A sennon of HCM Fourie with reference to the October Revolution in 1917 Doctor HCM Fourie, a theologian of the Nederduitsch Hervormde Kerk van Afrika, conducted several sermons in the years 1919—1938 concerning the danger that socialism entails. Under the heading 'Account', the method of investigation, as well as the problems concerning the study of a historical document, that is the written text of the sermon, is explained. The sermon is analized, and Fourie's criticism of socialism, valuated. Then follows the ultimate analysis of the historical document where the significance of this human effort is evaluated.